1987
DOI: 10.1088/0031-8949/36/3/023
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of ion-acoustic solitons into a weak localized magnetic field II - longitudinal field

Abstract: Experiments on the propagation of an ion-acoustic soliton from an isotropic plasma into a region containing a weak mirror magnetic field are described. An anomalous focusing of the soliton is detected. The magnetic field also allows us to separately observe reflected ions from the soliton and the ions involved in the excitation of the soliton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the magnetic field plays an important role 356 L. L. Yadav, R. S. Thvari and S. R. Sharma in modifying the characteristics of ion-acoustic solitons (Lee & Kan 1981;Yashvir, Bhatnagar & Sharma 1984;Raychaudhuri et al 1987;Yadav & Sharma 1990) and of double layers (Goswami & Bujarbarua 1985;Yadav & Sharma 1991). Two-electron-temperature distributions are very common in laboratory (Jones et al 1975) and space (Temerin et al 1982) plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the magnetic field plays an important role 356 L. L. Yadav, R. S. Thvari and S. R. Sharma in modifying the characteristics of ion-acoustic solitons (Lee & Kan 1981;Yashvir, Bhatnagar & Sharma 1984;Raychaudhuri et al 1987;Yadav & Sharma 1990) and of double layers (Goswami & Bujarbarua 1985;Yadav & Sharma 1991). Two-electron-temperature distributions are very common in laboratory (Jones et al 1975) and space (Temerin et al 1982) plasmas.…”
Section: Introductionmentioning
confidence: 99%